2007
DOI: 10.1099/vir.0.83184-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic drift in the evolution of H1N1 influenza A viruses resulting from deletion of a single amino acid in the haemagglutinin gene

Abstract: Two genetically distinct lineages of H1N1 influenza A viruses, circulated worldwide before 1994, were antigenically indistinguishable. In 1994, viruses emerged in China, including A/Beijing/262/ 95, with profound antigenic differences from the contemporary circulating H1N1 strains. Haemagglutinin sequence comparisons of either a predecessor virus, A/Hebei/52/94, or one representative of the cocirculating A/Bayern/7/95-like clade, A/Shenzhen/227/95, revealed a deletion of K at position 134 (H3 numbering) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…X31 and Philippines are each mouse-adapted reassortant strains. Beijing 262/95 is a relatively recent human clinical isolate that resembles modern H1N1 variants that emerged after 1994 (48) and has undergone relatively little selection in the laboratory. One might expect that the Beijing human isolate would be most greatly inhibited by LSTc decoy liposomes given its adaptation to the human airway, which has a high prevalence of ␣2-6-linked SA (49).…”
Section: Discussionmentioning
confidence: 99%
“…X31 and Philippines are each mouse-adapted reassortant strains. Beijing 262/95 is a relatively recent human clinical isolate that resembles modern H1N1 variants that emerged after 1994 (48) and has undergone relatively little selection in the laboratory. One might expect that the Beijing human isolate would be most greatly inhibited by LSTc decoy liposomes given its adaptation to the human airway, which has a high prevalence of ␣2-6-linked SA (49).…”
Section: Discussionmentioning
confidence: 99%
“…Additional residues have also been identified on the SAT serotypes (Crowther et al 1993b;Grazioli et al 2006), as well as others on related serotypes A, O, C and Asia1 which may also occur within the SAT serotypes (Grazioli et al 2013;Kitson et al 1990;Lea et al 1994;Saiz et al 1991). For the H1N1 virus, experimental studies have identified four major antigenic sites (Caton et al 1982), as well as a number of other sites known to be important (McDonald et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both natural immunity and vaccine-induced immunity are mediated primarily through antibodies against HA, in particular neutralizing antibodies that block the receptor binding ability of HA (25). In response to immune pressure exerted by neutralizing antibodies, viruses are able to “escape” through the accumulation of amino acid substitutions or, more rarely observed, amino acid deletions (26, 27). …”
Section: Introductionmentioning
confidence: 99%